A chalcogenide-cluster-based semiconducting nanotube array with oriented photoconductive behavior - Jiaqi Tang (Nature Portfolio, 2021)
Interesting properties of carbon nanotubes prompt a search for diverse inorganic nanotubes. Here, the authors report a supertetrahedral chalcogenide cluster-based semiconducting nanotube array that exhibits high electric conductivity and oriented photoconductive behavior.